1984
DOI: 10.1007/bf00008087
|View full text |Cite
|
Sign up to set email alerts
|

The mortality effect of ultraviolet radiation in a translucent and in a red morph ofAcanthodiaptomus denticornis (Crustacea, Copepoda) and its possible ecological relevance

Abstract: Ultraviolet radiation induced a lower mortality in morphs of A canthodiaptomus denticornis, coloured red by carotenoid pigments, than in translucent morphs. Calculations showed that ultraviolet penetration in a lake of low chlorophyll-a content may cause a hazardous dose in the surface layers. Experiments confirmed this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 8 publications
2
50
0
Order By: Relevance
“…For example, MAAs were in the highest concentrations in the warmest climates and lowest in the coldest climate, indicating that other selective forces apart from temperature are more important. Although it seems evident that carotenoids have photoprotective abilities, other benefits like nutritive value have also been suggested (Ringelberg and Hallegraeff 1976). In a series of studies Hairston (1979a), however, concluded that the photoprotection hypothesis is the most probable benefit of the carotenoid deposits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MAAs were in the highest concentrations in the warmest climates and lowest in the coldest climate, indicating that other selective forces apart from temperature are more important. Although it seems evident that carotenoids have photoprotective abilities, other benefits like nutritive value have also been suggested (Ringelberg and Hallegraeff 1976). In a series of studies Hairston (1979a), however, concluded that the photoprotection hypothesis is the most probable benefit of the carotenoid deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its strong antioxidant ability, astaxanthin is believed to protect zooplankton from photo-oxidative damage caused by high-energy irradiance (Hairston 1978). This view is supported by experimental studies showing the higher survival of intensely pigmented compared to transparent individuals exposed to ultraviolet (UV) or blue light (Hairston 1978, Ringelberg et al 1984, Davenport et al 2004). Furthermore, zooplankton have been shown to respond differentially to UV exposure, with lesspigmented species descending farther from the light source than more intensely pigmented ones (Rhode et al 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Melanin, which absorbs UVR directly, is mainly observed in arctic and alpine Daphnia, as well as in other cladocerans (Hessen and Sørensen 1990). Generally, pigmented species are less sensitive to solar radiation than unpigmented ones (Hairston 1976;Byron 1982;Ringelberg et al 1984).…”
mentioning
confidence: 99%